Ocena efektywności powiązań instytucji naukowych i badawczych z przedsiębiorstwami jako ważny element polityki innowacyjnej - Łącka, Irena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The article discusses the problem of evaluation of the effectiveness of the links between scientific sector units and enterprises. The authoress emphasizes its importance to the evaluation of domestic innovation policy and improvement in its effectiveness. The analysis of effectiveness of the links between those units is hindered because of occurrence of many impediments and limitations, presented elaborately in the article. Proper methodology of evaluation of the effectiveness of the connections between the participants of innovation process and the system of accumulation of data about their course, expenses and effects are due to be created. Modern methods of evaluation of the innovativeness are due to be used. The possession of proper and the most up to date information about the results of actions of innovation policy allows directing its future actions and improving the innovativeness of Polish economy.